Granting Hareuta Peunulang in Aceh: Between Grant and Inheritance - Miranti, Aufa; Nurhadi, Agus; Mohd Hiriy bin Ghazali Mohd Jani (DIKTUM: Jurnal Syariah dan Hukum, 2025)
Hareuta peunulang is a gift presented to a daughter getting married in Aceh as an immovable object. In practice, however, it is also given to the son. Some described it as a grant; on the other hand, others referred to it as an inheritance, resulting in legal inequality. This study aims to identify the problem of Islamic Law views on the giving and the practice of giving hareuta peunulang, which can be risk management for daughters in Aceh. It used an empirical method with a descriptive approach. Collecting data through interview techniques was conducted with 7 (seven) informants who were granted hareuta peunulang. The results show that it was determined that the practice was not contrary to favorable Islamic laws. The provisions of the limit of 1/3 of the assets described in KHI result from scholars' (Ulama) opinions based on benefit. The provision does not determine whether a grant is valid or not. Parental gifts can be considered as inheritance. In customary law, granting hareuta peunulang is a way to protect and provide welfare to women to avoid poverty and other risks. Acehnese has local wisdom to safeguard daughters, which is not contrary to Islamic law.